Loneliness in Elderly Who Lost The Partner - Djorsy, Ignacia Nabila; Suprayogi, Dedy; Suryani (International Conference on Sustainable Health Promotion, 2025)
Loneliness among the elderly is a common psychological issue, particularly among those who live alone. This phenomenon is important to study because loneliness can have a negative impact on mental health, reduce quality of life, and increase the risk of depression in the elderly. This study used a qualitative method with a phenomenological approach to explore the subjective experiences of the elderly in interpreting loneliness. The participants consisted of three elderly people over the age of 60 who lived alone in Sidoarjo. Data was collected through semi-structured interviews. The results of the study show that elderly people with introverted personalities tend to be more prone to loneliness, while those who are more outgoing are better able to cope with loneliness. Social support from the community plays an important role in reducing loneliness, while the loss of a partner is a major factor in the emergence of feelings of emptiness among elderly people who live alone.